DIGITAL BUSINESS MODEL OF THE AGRICULTURAL ORGANIZATION OF THE REGION - Anna LEKSINA; Aleksandr NESMYSLENOV; Maiya BRYZGALINA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of the work is to study the theoretical and applied aspects of digitalization of the agricultural sector for the formation of new management concepts and specific models. Their relevance is confirmed by their significance for the adoption of effective strategic decisions by the participants of the agricultural business. We used a combination of analytical and synthetic approaches, monographic, empirical, statistical-economic and abstract-logical research methods. The composition of the digital business model of an agricultural enterprise and its technological, information and management characteristics are determined. The principle of forming a process-oriented management system is applied. The novelty of the research consists in constructing the structure of the digital business model of the crop industry based on the digitalization of the technical, information and management components of its functioning and the industry-specific detailing of technologies. These elements of the business model are grouped and described for accounting of work and agricultural operations, monitoring of equipment, "assistant agronomist", reporting and analytics, cadastral accounting and scouting. The mechanism was studied and the results of the work of the agricultural organization of the region, which implements and develops digital technologies, were evaluated. The results obtained confirm the growth of economic efficiency in the implementation of digital technologies in agricultural production.